2002
DOI: 10.1016/s0735-1097(02)01717-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensive cholesterol reduction lowers blood pressure and large artery stiffness in isolated systolic hypertension

Abstract: Intensive cholesterol reduction may be beneficial in the treatment of patients with ISH and normal lipid levels, through a reduction in large artery stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
195
4
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(220 citation statements)
references
References 47 publications
10
195
4
11
Order By: Relevance
“…However, the 4.3 mmHg systolic and 1.6 mmHg reduction in diastolic blood pressure was unexpected. There is limited short-term trial evidence that atorvastatin treatment may reduce blood pressure in hypertensive and dyslipidaemic patients [30][31][32][33], possibly by improving endothelium-dependent vascular function [34]. A single uncontrolled trial [35] in patients with type 2 diabetes showed a 10 mmHg reduction in diastolic blood pressure, but this may partly be explained by habituation and regression to the mean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 4.3 mmHg systolic and 1.6 mmHg reduction in diastolic blood pressure was unexpected. There is limited short-term trial evidence that atorvastatin treatment may reduce blood pressure in hypertensive and dyslipidaemic patients [30][31][32][33], possibly by improving endothelium-dependent vascular function [34]. A single uncontrolled trial [35] in patients with type 2 diabetes showed a 10 mmHg reduction in diastolic blood pressure, but this may partly be explained by habituation and regression to the mean.…”
Section: Discussionmentioning
confidence: 99%
“…No consistent relationship between atorvastatin treatment and changes in glycated haemoglobin or other glycaemic measure has been reported in short-term trials that have examined the efficacy and safety of statin therapy in diabetic patients [30,[36][37][38][39]. These small studies, however, did not have the statistical power to identify HbA 1c changes as small as the 0.3% increase observed in AFORRD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that statins augment Akt activity in vessels, 40 improve blood flow by increasing NO synthase activation, 41 and may reduce vascular stiffening. 42 Statins also inhibit small GTPbinding proteins Rac1 and RhoA and thereby may impede development of cardiac hypertrophy. [43][44][45] Other strategies may involve enhancing NO synthase signaling by increasing substrate availability (arginase inhibition) or its cofactor tetrahydrobiopeterin (BH4).…”
Section: Destiffening Strategiesmentioning
confidence: 99%
“…Cholesterol lowering has been shown to improve arterial compliance in patients with familial hypercholesterolemia (Tomochika et al, 1996;Smilde et al, 2000) and hypertension (Ferrier et al, 2002). Stanol ester margarine lowers serum total and LDL cholesterol concentrations (Law 2000).…”
Section: Discussionmentioning
confidence: 99%